Answer:
f(1)=4
Step-by-step explanation:
f(1)=3(1)^4-(1)^2+4(1)-2
f(1)=3(1)-1+4-2
f(1)=3-1+4-2
f(1)=4
Angle 4 would be 77degrees because angle two is vertical to angle four.
Angle 3 and Angle 1 are equal because they are vertical to each other.
You would subtract 180 (degrees) minus 77 (degrees) and get 103 (degrees).
So Angle 3 and Angle 1 would both be 103 degrees.
You would get 180 degrees from the line.
Answer:
0/6 <--------------------------
Answer:
3
Step-by-step explanation:
The value of "a" is the coefficient of x^2, so we know that is 2.
__
<u>Solve for h</u>
Now, we have ...
2x^2 -8x +7 = 2(x -h)^2 +k
Expanding the right side gives us ...
= 2(x^2 -2hx +h^2) +k
= 2x^2 -4hx +2h^2 +k
Comparing x-terms, we see ...
-4hx = -8x
h = (-8x)/(-4x) = 2
__
<u>Solve for k</u>
Now, we're left with ...
2h^2 +k = 7 = 2(2^2) +k = 8 +k
Subtracting 8 we find k to be ...
k = 7 -8 = -1
__
And the sum of constants a, h, and k is ...
a +h +k = 2 +2 -1 = 3
The sum of the constants is 3.
Answer:
Step-by-step explanation:
3x - 6y = -1
-6y = -1 -3x
-6y = -(1+3x)
y = -(1+3x)/-6
y = (1 + 3x )/6